Uma abordagem sócio-histórica do léxico: estudo do item lexical empoderamento - Thaynara Nascimento Santos (2022)
This research aimed to analyze the lexical item empoderamento in the Portuguese language in texts obtained from the digital collection of the newspaper O Globo between 2003 and 2021. From a theoretical-methodological point of view, it was based on the theories of social lexicology (MATORÉ, 1953) and socio-historical lexicology (CAMBRAIA, 2013, 2020). In all, 834 occurrences were collected, divided into three subcorpora established by time frames: the first from 2003 to 2016 (S1); the second from 2017 to 2018 (S2); the third and last from 2019 to 2021 (S3). Four hypotheses were tested, all of which were confirmed: (a) the historical course of the lexical item empoderamento is related to social transformations; (b) sociolinguistic factors influenced the historical course of this lexical item; (c) there is the presence of antineologism in relation to this item in the analyzed corpus; and (d) this antineologism is ideological in nature.